International and cross-cultural management studies a postcolonial reading - Jack, Gavin, 1973- (Palgrave Macmillan, 2009)
"International and cross-cultural management has received very little critical attention to date. This book draws upon specific ideas from postcolonial theory to present a critique of these related academic fields. The authors argue that these management disciplines are Western discourses that exhibit historical as well as contemporary resonances with the vicissitudes of what might be broadly be called 'the colonial project'. The book explores alternative and perhaps more politically and morally constructive approaches to the question of the 'other' in late global capitalism"--Provided by publisher.